2017
DOI: 10.1089/omi.2017.0135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Proteomics and Cytokine Profiling for Dengue Fever Disease Severity Biomarkers

Abstract: Dengue fever (DF) is a major global health burden with a pathophysiology that is still incompletely understood. Biomarkers that predict and explain susceptibility to DF and its progression to its more severe hemorrhagic form are much needed. DF is endemic in tropical and subtropical regions of the world, with a rapidly increasing incidence of disease severity. We conducted a clinical biomarker discovery study using both a case-control and longitudinal study design. Plasma proteome alterations in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Those results also suggest that the high level of IP‐10, and low level of CXCL1 and platelets may play a role in the disruption of vascular endothelium resulting in vascular leakage after DENV infection. A recent study in plasma proteome using proteomics and cytokine profiling in dengue patients showed that an elevated level of IL‐1 RA, IL‐17, TNF‐α, MCP1‐MCAF, and MIP‐1β was observed only in the plasma of DHF patients . Previous studies of DENV2 infection on EA.hy926 cells reported transcellular transport to be affected rather than paracellular transport, whereas paracellular transport was observed to be profound in the cells treated with DENV2 and TNF‐α in the present study .…”
Section: Discussionsupporting
confidence: 48%
“…Those results also suggest that the high level of IP‐10, and low level of CXCL1 and platelets may play a role in the disruption of vascular endothelium resulting in vascular leakage after DENV infection. A recent study in plasma proteome using proteomics and cytokine profiling in dengue patients showed that an elevated level of IL‐1 RA, IL‐17, TNF‐α, MCP1‐MCAF, and MIP‐1β was observed only in the plasma of DHF patients . Previous studies of DENV2 infection on EA.hy926 cells reported transcellular transport to be affected rather than paracellular transport, whereas paracellular transport was observed to be profound in the cells treated with DENV2 and TNF‐α in the present study .…”
Section: Discussionsupporting
confidence: 48%
“…These proteins were found to play important role in disease pathology, for example α-1-acidglycoprotein is elevated during systemic tissue inflammation and is involved in neutrophil inactivation, chemotaxis, and oxidative metabolism (Pucadyil et al, 2004). The importance of plasma proteome profile for identification of disease specific protein biomarkers among various diseases were previously reported for Dengue patients (Jadhav et al, 2017), for Rheumatoid arthritis patients (Ohyama et al, 2012) and for VL patients (Bag et al, 2014). No such studies were reported previously for PKDL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines released mainly after T cell activation have been linked to the pathological events triggered by the infection 18,21,22 . SD has been associated with increased production of TNF-α, IFN-γ, IL-1ra, IL-4, IL-6, IL-10, CCL2, CCL3, CCL4, CXCL8 and CXCL10 2229 . In our study, the A-DENV group also showed increased levels of these molecules, except for CXCL10.…”
Section: Discussionmentioning
confidence: 99%